Green Metrics Evaluation on The Cannizzaro Reaction of p-Anisaldehyde and Benzaldehyde Under Solvent-Free Conditions - Firdaus, Maulidan; Firdausi, Nisrina Rahma; Rahmana, Desy Nila; Kusumaningsih, Triana (Jurnal Kimia Valensi, 2023)
In the pursuit of environmentally responsible chemical processes, we conducted a thorough assessment of the green metrics associated with the Cannizzaro reaction using p-anisaldehyde and benzaldehyde under solvent-free conditions. This research elaborates the application of two different methods i.e., reflux and ultrasonication, applying potassium hydroxide (KOH) as the reagent. The progress of the Cannizzaro reaction was methodically followed via thin-layer chromatography (TLC), and the resulting products were characterized using various techniques, including melting point analysis, Fourier-transform infrared spectroscopy (FTIR), and gas chromatography-mass spectrometry (GC/MS). To measure the environmental impact and sustainability of these reactions, a multifaceted approach was used. Green metrics were evaluated by the state-of-the-art Environmental Assessment Tool for Organic Syntheses (EATOS) software, combined with the Andraos algorithm. Moreover, energy consumption calculations were evaluated. Reasonable analysis of the green metrics results was undertaken in the framework of prevailing literature, permitting to measure the level of eco-friendliness attained. Experimental findings revealed optimal conditions for the Cannizzaro reaction concerning p-anisaldehyde at a temperature of 50 °C for 90 minutes, resulting in remarkable of p-anisyl alcohol and p-anisic acid in 95.16% and 95.04% yields, respectively. Likewise, the reaction involving benzaldehyde reached its peak performance at 50 °C for 2 hours, giving benzyl alcohol and benzoic acid in 96.17% and 97.22% yields, respectively. Overall, the green metrics assessment and energy consumption calculations reliably confirmed that the solvent-free Cannizzaro reaction, when performed via ultrasonication, offers a reasonably greener and more energy-efficient method than the traditional ones. This research highlights the importance of sustainable chemical synthesis practices and their potential to reduce the environmental footprint of chemical processes.